Critical Reflection and the Limits of Parental Authority. (Journal of Applied Philosophy, 2022)
In modern pluralist societies, the meaning and value of individual autonomy is highly contested. Typically, some religious groups deny the ideal of leading a self‐directed life and regard strict obedience to God's commands as the primary goal of child education. This article pursues the question of whether a liberal state may legitimately interfere with parental authority in order to protect the development of a child's inner capacity for autonomy. It is argued that the ability to critically re‐evaluate one's life plan is valuable for the offspring of secular and pious parents alike. Therefore, restrictions on parental rights can be justified within a liberal theoretical framework that is neutral between autonomous and heteronomous conceptions of the good. However, religious parents need not be prepared to call their most important tenets into question; they may foster their children's capacity for critical reflection in other ways. Since the vast majority of religious families meet this requirement, state interventions are rarely warranted.